2016
DOI: 10.1111/jcom.12237
|View full text |Cite
|
Sign up to set email alerts
|

Sexy, Strong, and Secondary: A Content Analysis of Female Characters in Video Games across 31 Years

Abstract: We analyzed in‐game content from titles released between 1983 and 2014 (n = 571) featuring playable female characters. Results indicate that sexualization has diminished since an observed height in the 1990s. Traditionally male‐oriented genres (e.g. fighting) have more sexualized characters than role‐playing games. Games rated Teen or Mature did not differ in sexualization and featured more sexualization than Everyone games. Despite an increase in games featuring playable female characters, games still depict … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
120
0
15

Year Published

2017
2017
2021
2021

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 178 publications
(136 citation statements)
references
References 38 publications
(75 reference statements)
1
120
0
15
Order By: Relevance
“…There is anecdotal evidence that the situation may have begun to change since 2009, with more female characters and stronger roles for them. One recent content analysis supports these anecdotal observations (Lynch, Tompkins, van Driel, & Fritz, ).…”
Section: Introductionmentioning
confidence: 63%
“…There is anecdotal evidence that the situation may have begun to change since 2009, with more female characters and stronger roles for them. One recent content analysis supports these anecdotal observations (Lynch, Tompkins, van Driel, & Fritz, ).…”
Section: Introductionmentioning
confidence: 63%
“…These games not only affect the way young women view themselves, they also encourage young men to look at women as sex objects (Dill and Thill 2007). Confirming these findings, another recent study (Lynch et al 2016) evaluated 571 playable female characters in video games released from 1989 to 2014 and concluded that despite an increase in games featuring playable female characters, games still depict female characters as sexualized and in more minor roles.…”
Section: Is Playing With Sexist Video Games Just Harmless Fun?mentioning
confidence: 87%
“…In addition, many video games that contain female characters sexually objectify them (Lynch, Tompkins, van Driel, & Fritz, 2016;Summers & Miller, 2014). Sexual objectification occurs when a person's body parts or functions are separated from the person, reduced to the status of instruments, or regarded as capable of representing the entire person (Gervais, Bernard, Klein, & Allen, 2013).…”
Section: Theoretical Foundations Of the Present Researchmentioning
confidence: 99%